 IMPLEMENTASI KEBIJAKAN DESENTRALISASI DAN DAYA SAING DAERAH DI KOTA SEMARANG - Yuwanto Yuwanto (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Indonesia has been undergoing a reform process. One of its features is the introduction of new decentralization policy and regulations enacted to develop the autonomy of local governments, including the fiscal balance between the central and local governments. This research attempts to reveal the impacts of decentralization practices on local competitiveness, as it is becoming one of the objectives of decentralization policy in Indonesia. By using a case study, this research was arranged to reveal the impacts of decentralization to local competitiveness in Semarang Municipality. The results showed that the impacts of decentralization on local competitiveness, either positive or negative, depend on how decentralization is practiced. Besides, the analysis found that decentralization has not yet provide an appropriate level of support to improve local competitiveness.Keywords: decentralization, local autonomy, local competitiveness